Library Software Awareness: A Survey of OPAC Vs Card Catalogue in IIT Delhi, IIT Kanpur, and Kashmir University - Ahmad, Hilal (DESIDOC Journal of Library & Information Technology, 2014)
The objective of this study is to highlight the library software awareness with special focus on OPAC Vs card catalogue among the users of Indian Institute of Technology (IIT) Delhi, IIT Kanpur, and Kashmir University. The study also highlights the features of LibSys and Virtua software used by the select libraries. The investigator has used questionnaire as a key tool for collecting the necessary data for the present study. Although the study covers a number of software packages, but Virtua and LibSys softwares have been discussed in detail. A wonderful finding of this study is that the Kashmir University has successfully installed RFID technology through Virtua; but, the same is yet to take place fully in the select IITs. However, the majority of users in select IITs are using OPAC, while as the usage of OPAC in Kashmir University is comparatively lesser. Another finding of this study is that all the select libraries are still maintaining card catalogues, though used very less. The present study will be useful to enhance the usage of OPAC in the select libraries. It will also serve as a tool for other libraries to analyse the features and facilities of leading indigenous and international software package for selecting the suitable software. http://dx.doi.org/10.14429/djlit.34.6164